Transcanal Microscopic Transpromontorial Approach for Vestibular Schwannoma - Isaacson, Brandon; Tolisano, Anthony M.; Patel, Ankur Ramanlal; Barnett, Samuel L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives This video demonstrates the transcanal transpromontorial approach for resection of vestibular schwannoma.Design/Setting/Participants Present study is based on a video of a single patient undergoing the above approach at a tertiary care skull base surgery program.Results This video demonstrates a transcanal microscopic transpromontorial approach for resection of an enlarging intracanalicular vestibular schwannoma in a young patient with nonserviceable hearing. The video highlights the pertinent surgical anatomy and outlines, in a step-by-step fashion, the approach to the internal auditory canal via this minimally invasive approach. The surgical indications and reconstructive techniques are also discussed (Fig. 1).Conclusions A transcanal microscopic transpromontorial approach for vestibular schwannoma is feasible and offers a minimally invasive option for patients electing for microsurgical resection.The link to the video can be found at: https://youtu.be/-oKkRooytws.
Keywords: vestibular schwannoma; lateral skull base; transpromontorial approach; minimally invasive